The Decentralisation of Health Management Systems through Small and Medium Enterprises in BRIC-Countries: A Semantic Model - Silvia Amato; Carol Yeh-Yun Lin (Asian Academy of Management Journal, 2012)
This article has been developed to provide an analytical framework about the process of health decentralisation that has emerged in BRIC-countries. For this purpose, this study offers a reflection about the process of decentralisation in emerging BRICs (Brazil, Russia, India and China) with theoretical argumentative issues about public health systems, and the reorganisation of the public health sector. The following review consequently focuses upon the managerial aspects of health systems, and SMEs' contribution to services delivery. In accordance, a semantic model organises current key determinants of involved actors in the public health sector for a contribution to understanding the affirmation of multiple forms of development in which the delivery of healthcare services has been critically implemented.